2007
DOI: 10.1111/j.1469-8749.2007.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological features of childhood cerebral infarction following varicella zoster virus infection

Abstract: The aim of the study was to describe the clinical and radiological features of childhood post-varicella cerebral infarction (PVCI). A retrospective review was undertaken of children with arterial ischaemic stroke (AIS) who had experienced varicella zoster virus (VZV) infection within the preceding year. Twenty-four children (15 males, nine females; age range at time of VZV infection 2mo-6y) were identified, with a median of 4 months between VZV and AIS (range 1wk-12mo). All had infarction in the middle cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 35 publications
5
68
0
2
Order By: Relevance
“…Consequently, the stenotic lesion of the artery affected might have been induced by the presence of adenovirus and subsequent inflammatory reaction. Furthermore, magnetic resonance imaging confirmed that the brain area afflicted with AIS in our patient was analogous to the areas involved in reported PVCI patients [13]. Thence, the morphology of the AIS provides additional argument for the proposed pathogenesis in our patient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consequently, the stenotic lesion of the artery affected might have been induced by the presence of adenovirus and subsequent inflammatory reaction. Furthermore, magnetic resonance imaging confirmed that the brain area afflicted with AIS in our patient was analogous to the areas involved in reported PVCI patients [13]. Thence, the morphology of the AIS provides additional argument for the proposed pathogenesis in our patient.…”
Section: Discussionsupporting
confidence: 84%
“…Granulomatous arteritis of the vessel wall causes post-varicella cerebral infarction (PVCI) and AIS after herpes zoster ophthalmicus [13]. Basilar artery aneurysm was also reported after varicella [14].…”
Section: Introductionmentioning
confidence: 99%
“…Better control of vascular risk factors in older patients presenting with TIA, which itself increases the risk of stroke, would also explain why, after HZ, the incidence of TIA but not stroke was increased in the THIN patient population as a whole. Together with published data linking stroke in children with recent history of chickenpox, [17][18][19] these results support a significant role for VZV, independently of other vascular risk factors, in the pathogenesis of stroke and cerebrovascular disease in the UK population, particularly at younger ages. The results are corroborated by population cohort studies conducted in Taiwan 4 and Denmark, 20 both of which identified HZ as a risk factor for stroke 4 or stroke plus TIA.…”
Section: Risk Factorsupporting
confidence: 76%
“…While most VZV vasculopathies develop within 6 weeks after zoster, the median interval for stroke is 4 months after varicella (16). Besides stroke and TIAs, patients may develop severe headache, cognitive impairment/confusion or unsteadiness.…”
Section: Clinical Laboratory and Imaging Features Of Vzv Vasculopathymentioning
confidence: 99%
“…PVA usually occurs in otherwise healthy, immunocompetent children and is usually monophasic, although progressive arteriopathy with recurrent TIA and stroke has been reported (11,16,24). As in adults, the CSF in children with VZV vasculopathy contains amplifiable VZV DNA or anti-VZV antibody, indicative of active infection (Table 1) and consistent with the detection of VZV antigen in granulomatous arteritis lesions of the left MCA of a 4-year-old girl who developed TIAs 8 months after varicella and died of malignant left hemispheric infarction 5 months later (15).…”
Section: Vzv Vasculopathy In Childrenmentioning
confidence: 99%